High-melt-flow polypropylene composition
A polypropylene composition with optimized crystalline and soluble fractions, produced via a multi-stage polymerization process, addresses the limitations of existing compositions by achieving high melt flow rates and improved mechanical and impact properties, suitable for injection molding.
Patent Information
- Application Number
- KR1020247020940
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-12-01
- Filing Date
- 2022-11-29
- Publication Date
- 2026-11-05
- Estimated Expiration
- 2042-11-29
AI Technical Summary
Existing heterogeneous polypropylene compositions with high melt flow rates (MFR) face limitations in mechanical properties, particularly stiffness and impurity issues, and lack an optimal balance of mechanical and impact properties suitable for injection molding of thin-walled articles.
A polypropylene composition is developed with a specific crystalline and soluble fraction ratio, optimized through a multi-stage polymerization process using a single-site catalyst system, achieving a high melt flow rate and improved mechanical and impact properties by controlling the intrinsic viscosity and ethylene content of these fractions.
The composition exhibits a high melt flow rate, excellent mechanical properties like flexural modulus and impact strength, and low impurity content, making it suitable for injection molding applications with enhanced processability and purity.
Smart Images

Figure 112024067857856-PCT00001 
Figure 112024067857856-PCT00002 
Figure 112024067857856-PCT00003
Abstract
Description
Technology Field
[0001] The present invention relates to a high melt flow polypropylene composition having an improved balance of properties in terms of mechanical properties and impact properties, a method for producing said polypropylene composition, an article comprising said polypropylene composition, and a use of said polypropylene composition for the production of the article. Background Technology
[0002] Lee Jong-sang (heterophasic) Propylene copolymers are widely used in the packaging industry due to their excellent combination of stiffness and impact behavior. Heterogeneous propylene copolymers can be applied in various aspects of daily life. One of the major applications of polypropylene can be found in the injection molding of thin-walled articles. Typical examples include plastic cups, buckets, and small containers primarily used for food packaging. To be suitable for thin-walled injection molding applications, polypropylene must exhibit excellent processability and flowability, which is generally expressed as a high melt flow rate (MFR), typically characterized by a low average molecular weight. Nevertheless, within the polymer and packaging industries, there is a need to improve available heterogeneous polypropylene compositions with high melt flow rates (MFR), taking into account mechanical properties and, in particular, the amount of impurities.
[0003] However, existing technology has several limitations. For example, heterogeneous polypropylene compositions with high melt flow rate (MFR) produced in the presence of a Ziegler-Natta catalyst have inherent limitations for the following two reasons:
[0004] First, the H2 reaction is poor, and the solubility of H2 and consequently the MFR are limited at the fixed temperature / pressure ratio of the reactor, especially when copolymers with ethylene are produced. Second, the amount of oligomers increases with the MFR. Although some techniques exist to remove oligomers from high-melt-flow heterogeneous polypropylene compositions, this can lead to other problems such as additive loss and has little effect on long-chain oligomers under normal conditions.
[0005] WO 2017 / 148970 A1 The present invention discloses heterogeneous polypropylene compositions having excellent mechanical and impact properties. However, the melt flow rate (MFR2) of these compositions is too low for some applications. Additionally, these compositions were prepared in the presence of a Ziegler-Natta catalyst and thus exhibit the limitations and impurities discussed above.
[0006] EP 3 812 404 A1 The present invention discloses heterogeneous polypropylene compositions having excellent mechanical and impact properties and low extractability. However, the melt flow rate (MFR2) of these compositions is too low for some applications.
[0007] EP 2 075 284 A1 The present invention discloses a heterogeneous polypropylene composition having a high melt flow rate MFR2. However, such compositions lack mechanical properties, particularly stiffness.
[0008] Accordingly, there is a need in the industry for a polypropylene composition having a high melt flow rate MFR2 of more than 100 g / 10 min suitable for injection molding and the manufacture of thin-walled articles, which shows an improved balance of properties in terms of mechanical and impact properties represented by high flexural modulus and impact strength, high processability exemplified by high melt flow rate, and low impurity content exemplified by low amounts of VOC and FOG.
[0009] It was surprisingly discovered that a polypropylene composition having this improved balance of properties can be obtained by carefully selecting the polymerization conditions of the polypropylene composition and thereby optimizing the properties of the elastomer phase identified as the soluble phase (SF) in CRYSTEX measurements.
[0010] The present invention relates to a polypropylene composition comprising both a crystalline fraction (CF) and a soluble fraction (SF) upon determination according to CRYSTEX QC analysis, wherein
[0011] Thus, the above availability fraction (SF)
[0012] · Present in the polypropylene composition in an amount ranging from 10.0 to 35.0 weight%, preferably from 11.0 to 32.5 weight%, and more preferably from 12.0 to 30.0 weight%, based on the total weight of the polypropylene composition,
[0013] · Having an intrinsic viscosity (iV(SF)) of at least 2.0 dl / g, preferably in the range of 2.3 to 4.5 dl / g, more preferably in the range of 2.5 to 4.3 dl / g, and
[0014] · Quantitative 13 Having an ethylene content (C2(SF)) in the range of 14.0 to 29.0 wt%, preferably in the range of 17.0 to 26.0 wt%, more preferably in the range of 19.0 to 24.0 wt%, based on the total weight of the soluble fraction (SF) as determined by FT-IR spectroscopy corrected by C-NMR spectroscopy;
[0015] The ratio of the intrinsic viscosity of the soluble fraction to the intrinsic viscosity of the crystalline fraction (iV(SF) / (iV(CF))) is in the range of 2.5 to 5.0, preferably in the range of 2.6 to 4.8;
[0016] The polypropylene composition has a melt flow rate MFR2 (230°C, 2.16 kg, ISO 1133) in the range of 105 to 320 g / 10 min, preferably in the range of 107 to 300 g / 10 min, more preferably in the range of 110 to 280 g / 10 min.
[0017] In addition, the present invention relates to a method for producing a polypropylene composition as described above or below, wherein
[0018] a) a step of polymerizing propylene in a first polymerization reactor in the presence of a single-site catalyst system to produce a first propylene polymer fraction;
[0019] b) a step of transferring a polymerization mixture comprising a single-site catalyst system and a first propylene polymer fraction from a first polymerization reactor to a second polymerization reactor;
[0020] c) a step of polymerizing propylene in a second polymerization reactor in the presence of a single-site catalyst system to produce a second propylene polymer fraction;
[0021] d) a step of transferring a polymerization mixture comprising a single-site catalyst system and first and second propylene polymer fractions from a second polymerization reactor to a third polymerization reactor;
[0022] e) a step of polymerizing propylene and ethylene in a third polymerization reactor in the presence of a single-site catalyst system to produce a third propylene-ethylene copolymer fraction;
[0023] f) withdrawing a polymerization mixture comprising a single-site catalyst system, first and second propylene polymer fractions and a third propylene-ethylene copolymer fraction from a third polymerization reactor; and
[0024] g) a step of obtaining a polymer composition comprising first and second propylene polymer fractions and a third propylene-ethylene copolymer fraction.
[0025] In addition, the present invention relates to an article comprising a polypropylene composition as described above or below.
[0026] Finally, the present invention relates to the use of a polypropylene composition as described above or below for the production of articles.
[0027] definition
[0028] Propylene homopolymers are polymers composed essentially of propylene monomer units. In particular, due to impurities during the commercial polymerization process, propylene homopolymers may contain up to 0.1 mol% comonomer units, preferably up to 0.05 mol% comonomer units, and most preferably up to 0.01 mol% comonomer units.
[0029] The propylene random copolymer consists of propylene monomer units and, preferably, ethylene and C4-C 10 It is a copolymer of comonomer units selected from alpha-olefins, wherein the comonomer units are randomly distributed in the polymer chain. The propylene random copolymer may comprise comonomer units from one or more comonomers having different amounts of carbon atoms.
[0030] Heterogeneous polypropylene is a propylene-based copolymer having a semicrystalline matrix phase, which may be a propylene homopolymer or a random copolymer of propylene and at least one alpha-olefin comonomer, and an elastomer phase dispersed therein. In the case of a random heterogeneous propylene copolymer, the semicrystalline matrix phase is a random copolymer of propylene and at least one alpha-olefin comonomer.
[0031] The elastomeric phase may be a propylene copolymer having a large amount of comonomers distributed in comonomer-rich block structures and propylene-rich block structures, rather than being randomly distributed in the polymer chains. Heterophasic polypropylene is generally distinguished from monophasic propylene copolymers in that it exhibits two distinct glass transition temperatures Tg attributed to the matrix phase and the elastomeric phase.
[0032] In the following, amounts are expressed in weight % (wt-%) unless otherwise specified. Specific details for implementing the invention
[0033] Polypropylene composition
[0034] In one embodiment, the present invention relates to a polypropylene composition having a high melt flow rate that exhibits high fluidity and excellent processability. Accordingly, the polypropylene composition is suitable for injection molding and thin-wall applications.
[0035] The polypropylene composition has MFR2 (230°C, 2.16 kg, ISO 1133) in the range of 105 to 320 g / 10 min, preferably in the range of 107 to 300 g / 10 min, more preferably in the range of 110 to 280 g / 10 min.
[0036] Polypropylene compositions can be characterized by CRYSTEX QC analysis. In CRYSTEX QC analysis, crystalline fractions (CF) and soluble fractions (SF) are obtained, which can be quantified and analyzed in relation to intrinsic viscosity (iV) as well as monomer and comonomer content.
[0037] The polypropylene composition preferably exhibits one or all of the following characteristics in CRYSTEX QC analysis:
[0038] - When determined according to CRYSTEX QC analysis, in the range of 65.0 to 90.0 weight% based on the total weight of the polypropylene composition, preferably in the range of 67.5 to 89.0 weight%, more preferably A crystalline fraction (CF) content in the range of 70.0 to 88.0 weight%, and
[0039] - Content of a soluble fraction (SF) in the range of 10.0 to 35.0 weight%, preferably 11.0 to 32.5 weight%, and more preferably 12.0 to 30.0 weight% based on the total weight of the polypropylene composition as determined by CRYSTEX QC analysis.
[0040] The crystalline fraction (CF) preferably has one or more of the following characteristics, preferably all of them:
[0041] - Quantitative 13 Ethylene content (C2(CF)) of 1.0 wt% or less, preferably in the range of 0 to 0.9 wt%, based on the total weight of the crystalline fraction (CF) as determined by FT-IR spectroscopy corrected by C-NMR spectroscopy; and / or
[0042] - Intrinsic viscosity (iV(CF)) of 1.2 dl / g or less, preferably in the range of 0.4 to 1.1 dl / g, when measured in decalin at 135°C according to DIN ISO 1628 / 1.
[0043] The above availability fraction (SF) has the following characteristics:
[0044] - Quantitative 13 ethylene content (C2(SF)) in the range of 14.0 to 29.0 wt%, preferably in the range of 17.0 to 26.0 wt%, more preferably in the range of 19.0 to 24.0 wt% based on the total weight of the soluble fraction (SF) as determined by FT-IR spectroscopy corrected by C-NMR spectroscopy; and / or
[0045] - Intrinsic viscosity (iV(SF)) of at least 2.0 dl / g, preferably in the range of 2.3 to 4.5 dl / g, more preferably in the range of 2.5 to 4.3 dl / g, when measured in decalin according to DIN ISO 1628 / 1 at 135℃.
[0046] The ratio of the intrinsic viscosity of the soluble fraction to the intrinsic viscosity of the crystalline fraction (iV(SF) / (iV(CF))) is in the range of 2.5 to 5.0, preferably in the range of 2.6 to 4.8.
[0047] The polypropylene composition is preferably quantitative 13 It contains a total ethylene (C2) content in the range of 2.0 to 5.5 weight%, preferably 2.5 to 5.0 weight%, based on the total weight of the polypropylene composition as determined by FT-IR spectroscopy corrected by C-NMR spectroscopy.
[0048] In addition, the polypropylene composition preferably has an intrinsic viscosity (iV) in the range of 0.8 to 1.8 dl / g, more preferably in the range of 1.0 to 1.4 dl / g, when measured in decalin at 135°C according to DIN ISO 1628 / 1.
[0049] Preferably, the polypropylene composition comprises a fraction (XCS) soluble in cold xylene at 25°C in a range of 8.0 to 32.0 weight%, preferably 9.0 to 30.0 weight%, and more preferably 10.0 to 28.0 weight% based on the total weight of the polypropylene composition.
[0050] The above XCS fraction preferably has one or both of the following characteristics:
[0051] · Intrinsic viscosity (iV(XCS)) of at least 2.2 dl / g, preferably in the range of 2.3 to 4.6 dl / g, more preferably in the range of 2.5 to 4.4 dl / g, and / or
[0052] · Quantitative 13 Ethylene content (C2(XCS)) in the range of 15.0 to 30.0 wt%, preferably in the range of 18.0 to 27.0 wt%, more preferably in the range of 20.0 to 25.0 wt%, based on the total weight of the soluble fraction (SF) as determined by FT-IR spectroscopy corrected by C-NMR spectroscopy.
[0053] It is preferable that the polypropylene composition has a melting temperature (Tm) in the range of 150°C to 162°C, more preferably in the range of 152°C to 160°C, when determined by DSC according to ISO 3146 (Part 3, Method C2).
[0054] In addition, the polypropylene composition has a crystallization temperature (Tc) that is preferably in the range of 110°C to 130°C and more preferably in the range of 115°C to 125°C when determined by DSC according to ISO 3146 (Part 3, Method C2).
[0055] In addition, the polypropylene composition has a melting enthalpy (Hm) in the range of 80 to 100 J / g, more preferably in the range of 85 to 95 J / g, when determined by DSC according to ISO 3146 (Part 3, Method C2).
[0056] The polypropylene composition according to the present invention preferably exhibits an excellent balance of properties with respect to mechanical properties such as a high flexural modulus and impact properties such as high Charpy notch impact strength. Accordingly, the flexural modulus and Charpy notch impact strength depend on the amount of the soluble fraction (SF) of the polypropylene composition, which reflects the elastomer content of the polypropylene composition, and the melt flow rate MFR2. It has been found that the polypropylene composition exhibits a high flexural modulus depending on the amount of the soluble fraction (SF) and a high Charpy notch impact strength depending on the melt flow rate MFR2.
[0057] The composition is preferably an injection molded test specimen (80 x 10 x 4 mm) produced according to EN ISO 1873-2. 3 When determined according to ISO 178, it has a bending modulus in the range of 800 MPa to 1500 MPa, preferably in the range of 850 MPa to 1450 MPa.
[0058] It is desirable for the polypropylene composition to have a bending modulus (FM) that satisfies the following equation in relation to the amount of the soluble fraction (SF).
[0059]
[0060] Preferably
[0061]
[0062] More preferably
[0063]
[0064] Most preferably
[0065]
[0066] At this time,
[0067] FM[MPa] is the flexural modulus of the polypropylene composition, MPa, and
[0068] The amount (SF) [weight%] is the amount of the soluble fraction (SF) of the polypropylene composition, in weight%.
[0069] In addition, the composition is preferably an injection-molded test specimen (80 x 10 x 4 mm) produced according to EN ISO 1873-2. 3 2.5 to 15.0 kJ / m² at 23℃ when determined according to ISO 179 / eA for ) 2 Range, preferably 3.0 to 12.0 kJ / m² 2 It has a range of Charpy notch impact strength.
[0070] It is preferable that the polypropylene composition has a Charpy notch impact strength at 23°C (CNIS, 23°C), which satisfies the following equation in relation to the melt flow rate (MFR2).
[0071]
[0072] Preferably
[0073]
[0074] More preferably
[0075]
[0076] Most preferably
[0077]
[0078] In addition to an excellent balance of mechanical and impact properties, the polypropylene composition further exhibits high purity, which can be seen even in low amounts of VOCs and FOG.
[0079] The polypropylene composition preferably has a volatile organic compound (VOC) content of 50 μg / g or less, preferably 40 μg / g or less, and more preferably 35 μg / g or less when determined according to VDA 278.
[0080] The lower limit of VOC content is generally at least 2 μg / g, preferably at least 4 μg / g.
[0081] In addition, the polypropylene composition has an FOG content of preferably 300 μg / g or less, preferably 250 μg / g or less, and more preferably 225 μg / g or less when determined according to VDA 278.
[0082] The lower limit of the FOG content is typically at least 20 μg / g, preferably at least 40 μg / g.
[0083] The polypropylene composition preferably comprises a heterophase propylene copolymer comprising a semicrystalline matrix phase and an elastomer phase dispersed on said matrix.
[0084] It is preferable that the polypropylene composition comprises an amount of heterophase propylene copolymer in the range of 93.0 to 100 weight%, preferably 95.0 to 99.9 weight%, and more preferably 96.5 to 99.8 weight%, based on the total weight of the polypropylene composition.
[0085] The polypropylene composition may include additional polymer components. However, it is preferable that the polypropylene composition include a heteropolymer as a homopolymer component.
[0086] The polypropylene composition may additionally include an additive in an amount of 0.01 to 7.0 weight%, preferably 0.1 to 5.0 weight%, and more preferably 0.2 to 3.5 weight% based on the total weight of the polypropylene composition.
[0087] Generally, additives will be selected from antioxidants, anti-slip agents, nucleating agents, anti-scratch agents, anti-stick agents, metal inerts, UV stabilizers, acid removers, lubricants, antistatic agents, pigments, etc., as well as combinations thereof. These additives are well known in the polymer industry, and their use will be familiar to skilled practitioners. Any existing additive may be added as isolated raw material or as a mixture with the carrier polymer, that is, as a so-called masterbatch.
[0088] method
[0089] In a further embodiment, the present invention relates to a method for producing a polypropylene composition as described above or below, wherein
[0090] a) a step of polymerizing propylene in a first polymerization reactor in the presence of a single-site catalyst system to produce a first propylene polymer fraction;
[0091] b) a step of transferring a polymerization mixture comprising a single-site catalyst system and a first propylene polymer fraction from a first polymerization reactor to a second polymerization reactor;
[0092] c) a step of polymerizing propylene in a second polymerization reactor in the presence of a single-site catalyst system to produce a second propylene polymer fraction;
[0093] d) a step of transferring a polymerization mixture comprising a single-site catalyst system and first and second propylene polymer fractions from a second polymerization reactor to a third polymerization reactor;
[0094] e) a step of polymerizing propylene and ethylene in a third polymerization reactor in the presence of a single-site catalyst system to produce a third propylene-ethylene copolymer fraction;
[0095] f) withdrawing a polymerization mixture comprising a single-site catalyst system, first and second propylene polymer fractions and a third propylene-ethylene copolymer fraction from a third polymerization reactor; and
[0096] g) a step of obtaining a polymer composition comprising first and second propylene polymer fractions and a third propylene-ethylene copolymer fraction.
[0097] The first polymerization reactor is preferably a slurry-phase reactor, such as a loop reactor.
[0098] The operating temperature of the first polymerization reactor, preferably the loop reactor, is preferably in the range of 62°C to 85°C, more preferably 65°C to 82°C, and even more preferably 67°C to 80°C.
[0099] Generally, the pressure in the first polymerization reactor, preferably the loop reactor, is in the range of 20 to 80 bar, preferably 30 to 70 bar, for example, 35 to 65 bar.
[0100] It is desirable that a propylene homopolymer be produced in a first polymerization reactor, preferably a loop reactor. Accordingly, it is desirable that the first propylene polymer fraction be a propylene homopolymer fraction.
[0101] Preferably, hydrogen is added to the first polymerization reactor to control the molecular weight, i.e., the melt flow rate MFR2.
[0102] Preferably, the hydrogen to propylene ratio (H2 / C3 ratio) in the first polypropylene reactor, preferably the loop reactor, is in the range of 0.70 to 2.5 mol / kmol, more preferably 0.75 to 2.0 mol / kmol.
[0103] Due to the strong hydrogen reaction of the catalyst and a somewhat large amount of hydrogen, the melt flow rate of the first propylene polymer fraction is very high.
[0104] The first propylene polymer fraction preferably has a melt flow rate MFR2 (230°C, 2.16 kg, ISO 1133) in the range of 1000 to 15000 g / 10 min, preferably in the range of 1100 to 13500 g / 10 min, more preferably in the range of 1250 to 11500 g / 10 min.
[0105] The second polymerization reactor is preferably a first gas phase reactor, such as the first fluidized bed gas phase reactor.
[0106] The operating temperature of the second polymerization reactor, preferably the first gas phase reactor, is preferably in the range of 75°C to 95°C, more preferably in the range of 78°C to 92°C.
[0107] Generally, the pressure of the second polymerization reactor, preferably the first gas phase reactor, is in the range of 5 to 50 bar, preferably 15 to 40 bar.
[0108] Preferably, a propylene homopolymer is produced in a second polymerization reactor, preferably in a first gas phase reactor. Accordingly, it is preferable that the second propylene polymer fraction is a propylene homopolymer fraction.
[0109] Preferably, hydrogen is added to the second polymerization reactor to control the molecular weight, i.e., the melt flow rate MFR2.
[0110] Preferably, the hydrogen to propylene ratio (H2 / C3 ratio) in the second polypropylene reactor, preferably the first gas phase reactor, is in the range of 2.0 to 6.5 mol / kmol, more preferably 2.8 to 5.5 mol / kmol.
[0111] Due to the strong hydrogen reaction of the catalyst and a somewhat large amount of hydrogen, the melt flow rate of the combined first and second propylene polymer fractions is very high.
[0112] It is preferable that the combined first and second propylene polymer fractions have a melt flow rate MFR2 (230°C, 2.16 kg, ISO 1133) of at least 1000 g / 10 min, preferably in the range of 1200 to 9000 g / 10 min, more preferably in the range of 1500 to 8000 g / 10 min.
[0113] It is more preferable that the combined first and second propylene polymer fractions have a fraction soluble in cold xylene at 25°C (XCS) in an amount of 2.0% by weight or less, preferably in the range of 0.1 to 1.5% by weight, based on the total weight of the combined first and second propylene polymer fractions.
[0114] The third polymerization reactor is preferably the second gas phase reactor, for example, the second fluidized bed gas phase reactor.
[0115] The operating temperature of the third polymerization reactor, preferably the second gas phase reactor, is preferably in the range of 65°C to 85°C, more preferably 68°C to 82°C. In general, the operating temperature of the third polymerization reactor is lower than the operating temperature of the second polymerization reactor.
[0116] Generally, the pressure of the third polymerization reactor, preferably the second gas phase reactor, is in the range of 5 to 50 bar, preferably 15 to 40 bar.
[0117] A propylene-ethylene copolymer is produced in a third polymerization reactor, preferably a second gas phase reactor. Thus, the third propylene polymer fraction is a propylene-ethylene copolymer fraction.
[0118] In the third polymerization reactor, preferably the second gas phase reactor, the ethylene to propylene ratio (C2 / C3 ratio) is in the range of 700 to 1000 mol / kmol, more preferably 800 to 950 mol / kmol.
[0119] Due to the high ethylene-to-propylene ratio (C2 / C3 ratio), the third propylene copolymer fraction is preferably an elastomeric block copolymer having a propylene-rich compartment and an ethylene-rich compartment.
[0120] Preferably, hydrogen is added to the second polymerization reactor to control the molecular weight, i.e., the melt flow rate MFR2.
[0121] Preferably, in the third polymerization reactor, preferably the second gas phase reactor, the hydrogen to ethylene ratio (H2 / C2 ratio) is in the range of 0.5 to 3.5 mol / kmol, more preferably 1.0 to 2.5 mol / kmol.
[0122] It is preferable that the combined first, second, and third propylene polymer fractions have a melt flow rate MFR2 (230°C, 2.16 kg, ISO 1133) of at least 150 g / 10 min, preferably in the range of 165 to 500 g / 10 min, and more preferably in the range of 175 to 400 g / 10 min.
[0123] In addition, the combined first, second, and third propylene polymer fractions preferably have a fraction (XCS) soluble in cold xylene at 25°C in a range of 8.0 to 32.0 wt%, preferably 9.0 to 30.0 wt%, and more preferably 10.0 to 28.0 wt% based on the total weight of the polypropylene composition, and the XCS fraction preferably has the following characteristics:
[0124] · Intrinsic viscosity (iV(XCS)) in the range of at least 2.2 dl / g, preferably 2.3 to 4.6 dl / g, more preferably 2.5 to 4.4 dl / g,
[0125] · Quantitative 13 Ethylene content (C2(XCS)) in the range of 15.0 to 30.0 wt%, preferably 18.0 to 27.0 wt%, more preferably 20.0 to 25.0 wt% based on the total weight of the soluble fraction (SF) as determined by FT-IR spectroscopy corrected by C-NMR spectroscopy.
[0126] In addition, the combined first, second, and third propylene polymer fractions are preferably quantitative 13 The total comonomer content is in the range of 2.0 to 5.5 weight%, preferably 2.5 to 5.0 weight%, based on the total weight of the polypropylene composition when determined by FT-IR spectroscopy corrected by C-NMR spectroscopy.
[0127] The combined first, second, and third propylene polymer fractions preferably form a heterogeneous propylene copolymer.
[0128] The preparation of the first, second, and third propylene polymer fractions may include prepolymerization in a prepolymerization reactor upstream of the first polymerization reactor in addition to at least three prepolymerization (major) polymerization steps.
[0129] Polypropylene is produced in a prepolymerization reactor. Prepolymerization is preferably carried out in the presence of a single-site polymerization catalyst system. According to this embodiment, the single-site polymerization catalyst system is introduced in the prepolymerization step. However, this does not exclude the option of adding an additional co-catalyst in a subsequent step, for example, to the polymerization process, for example, to the first reactor. In one embodiment, all components of the single-site catalyst are added to the prepolymerization reactor only when prepolymerization is applied.
[0130] The prepolymerization reaction is generally carried out at a temperature of 0°C to 60°C, preferably 15°C to 50°C, more preferably 20°C to 45°C.
[0131] The pressure inside the prepolymerization reactor is not critical, but it must be high enough to maintain the reaction mixture in a liquid phase. Thus, the pressure can be 20 to 100 bar, for example, 30 to 70 bar.
[0132] In a preferred embodiment, the prepolymerization is carried out as bulk slurry polymerization in liquid propylene, i.e., the liquid phase consists mainly of propylene, and optionally an inert component is dissolved.
[0133] Other components may also be added during the prepolymerization step. Thus, as is known in the art, the molecular weight of polypropylene can be controlled by adding hydrogen during the prepolymerization step. Additionally, antistatic additives may be used to prevent particles from adhering to each other or to the reactor walls.
[0134] Precise control of prepolymerization conditions and reaction parameters is within the technical scope of the industry.
[0135] Due to the process conditions defined above in the prepolymerization, a mixture of a single-site catalyst system and polypropylene produced in the prepolymerization reactor is preferably obtained. Preferably, the single-site catalyst system is (finely) dispersed in the polypropylene. In other words, the single-site catalyst particles introduced into the prepolymerization reactor are divided into smaller pieces evenly distributed within the growing polypropylene. The size of the introduced single-site catalyst particles and the obtained pieces is not essential to the present invention and is within the knowledge of the skilled.
[0136] As mentioned above, when prepolymerization is used, following the prepolymerization, a mixture of the single-site catalyst and polypropylene produced in the prepolymerization reactor is transferred to the first polymerization reactor. Generally, the total amount of polypropylene produced in the prepolymerization reactor is somewhat low in the first, second, and third propylene polymer fractions, generally 5.0 wt% or less, more preferably 4.0 wt% or less, even more preferably in the range of 0.5 to 4.0 wt%, for example, in the range of 1.0 to 3.0 wt%.
[0137] If prepolymerization is not used, other components such as propylene and a single-site catalyst system are introduced directly into the first polymerization reactor.
[0138] At various polymerization stages, the residence time of the polymerization mixture is adjusted to obtain amounts of the first, second, and third polymer fractions in the combined first, second, and third polymer fractions.
[0139] Preferably, the first propylene polymer fraction is present in an amount of 40 to 60 weight%, more preferably 45 to 55 weight%, based on the total weight of the combined first, second, and third propylene polymer fractions. The amount of polypropylene produced in the prepolymerization reactor is generally added to the amount of the first propylene polymer fraction.
[0140] Preferably, the second propylene polymer fraction is present in an amount of 25 to 45 weight%, more preferably 30 to 40 weight%, based on the total weight of the combined first, second, and third propylene polymer fractions.
[0141] Preferably, the third propylene polymer fraction is present in an amount of 10 to 30 weight%, more preferably 15 to 25 weight%, based on the total weight of the combined first, second, and third propylene polymer fractions.
[0142] Catalytic system
[0143] The single-site catalyst system according to the present invention may be any supported metallocene catalyst system suitable for the production of isotactic polypropylene.
[0144] A single-site catalyst system comprises a co-catalyst system including a metallocene complex, a boron-containing co-catalyst and / or an aluminoxan co-catalyst, and It is desirable to include a silica support.
[0145] In particular, the single-site catalyst system preferably includes the following:
[0146] (i) Metallocene complex of chemical formula (I):
[0147]
[0148] In the above chemical formula (I),
[0149] Each X is independently a sigma-donor ligand, and
[0150] L is a divalent bridge selected from -R'2C-, -R'2C-CR'2-, -R'2Si-, -R'2Si-SiR'2-, and -R'2Ge-, and each R' independently optionally contains a hydrogen atom or one or more heteroatoms from groups 14 to 16 of the periodic table, C1-C 20 - It can be a hydrocarbyl group or a fluorine atom, or optionally two R' groups can be taken together to form a ring, and
[0151] Each R 1 may be independently the same or different, and may be hydrogen, linear or branched C1-C6-alkyl groups, C 7-20 -arylalkyl, C 7-20 -alkylaryl group or C 6-20 - It is an aryl or OY group, and Y is C 1-10 - It is a hydrocarbil group, and optionally 2 adjacent R 1 The group may be a part of a ring containing a phenyl carbon to which it is bonded, and
[0152] Each R 2It may be independently the same or different, and CH2-R 8 It is, and at this time R 8 is H or linear or branched C 1-6 -alkyl group, C 3-8 -cycloalkyl group, C 6-10 -Arilgigo,
[0153] R 3 is a linear or branched C1-C6-alkyl group, C 7-20 -arylalkyl, C 7-20 -alkylaryl group or C6-C 20 - It is Arilgi, and
[0154] R 4 is C(R 9 It is stage 3, and at this time R 9 is a linear or branched C1-C6-alkyl group, and
[0155] R 5 It is an aliphatic C1-C that selectively contains hydrogen or one or more heteroatoms from Groups 14 to 16 of the periodic table. 20 - It is a hydrocarbyl group;
[0156] R 6 Aliphatic C1-C that optionally contains hydrogen or one or more heteroatoms from Groups 14 to 16 of the periodic table 20 - Hydrocarbyl group or;
[0157] R 5 and R 6 They can be taken together to form a 5-membered saturated carbon ring, which consists of n groups R 10 Optionally substituted by, where n is 0 to 4;
[0158] Each R 10 is identical or different, and C1-C 20 - A C1-C optionally containing a hydrocarbyl group, or one or more heteroatoms belonging to groups 14 to 16 of the periodic table 20 - It may be a hydrocarbyl group;
[0159] R 7H or a linear or branched C1-C6-alkyl group or 1 to 3 R 11 It is an aryl or heteroaryl group having 6 to 20 carbon atoms that is selectively substituted by a group, and
[0160] Each R 11 may be independently the same or different, and may be hydrogen, linear or branched C1-C6-alkyl groups, C 7-20 -arylalkyl, C 7-20 -alkylaryl group or C 6-20 - It is an aryl or OY group, and Y is C 1-10 -Hydrocarbilgime,
[0161] (ii) a co-catalyst system comprising a boron-containing co-catalyst and / or an aluminoxane co-catalyst, and
[0162] (iii) Silica support.
[0163] The term "sigma-donor ligand" is well known to those skilled in the art, namely, a group bonded to a metal via a sigma bond. Therefore, the anionic ligand "X" may independently be a halogen or selected from the group consisting of R', OR', SiR'3, OSiR'3, OSO2CF3, OCOR', SR', NR'2, or PR'2 groups, and R' may independently be hydrogen, linear or branched, cyclic or acyclic, C1 to C2 20 Alkyl, C2 to C 20 Alkenyl, C2 to C 20 Alkynyl, C3 to C 12 Cycloalkyl, C6 to C 20 Aryl, C7 to C 20 Arylalkyl, C7 to C 20 Alkylaryl, C8 to C 20 It may be selected from the group consisting of aryl alkenyls, and the R' group may optionally contain one or more heteroatoms belonging to groups 14 to 16. In a preferred embodiment, the anionic ligand "X" is the same and is a halogen such as Cl, methyl or benzyl.
[0164] Desirable monovalent anionic ligands are halogens, particularly chlorine (Cl).
[0165] Desirable metallocene complexes include the following:
[0166] rac-dimethylsilanediylbis[2-methyl-4-(3',5'-dimethylphenyl)-5-methoxy-6-tert-benzylidene-1-yl]zirconium dichloride,
[0167] rac-anti-dimethylsilanediyl[2-methyl-4-(4'-tert-butylphenyl)-indene-1-yl][2-methyl-4-(4'-tert-butylphenyl)-
[0168] 5-methoxy-6-tert-benzylidene-1-yl]zirconium dichloride,
[0169] rac-anti-dimethylsilanediyl[2-methyl-4-(4'-tert-butylphenyl)-indene-1-yl][2-methyl-4-phenyl-5-methoxy-6-tert-benzylidene-1-yl] zirconium dichloride,
[0170] rac-anti-dimethylsilanediyl[2-methyl-4-(3',5'-tert-butylphenyl)-1,5,6,7-tetrahydro-sindacen-1-yl][2-methyl-4-(3',5'-dimethyl-phenyl)-5-methoxy-6-tert-benzylidene-1-yl] zirconium dichloride,
[0171] rac-anti-dimethylsilanediyl[2-methyl-4,8-bis-(4'-tert-butylphenyl)-1,5,6,7-tetrahydro-sindacen-1-yl][2-methyl-4-(3',5'-dimethyl-phenyl)-5-methoxy-6-tert-benzylidene-1-yl] zirconium dichloride,
[0172] rac-anti-dimethylsilanediyl[2-methyl-4,8-bis-(3',5'-dimethylphenyl)-1,5,6,7-tetrahydro-s-indacene-1-yl] [2-methyl-4-(3',5'-dimethylphenyl)-5-methoxy-6-tert-benzylidene-1-yl] zirconium dichloride,
[0173] rac-anti-dimethylsilanediyl[2-methyl-4,8-bis-(3',5'-dimethylphenyl)-1,5,6,7-tetrahydro-s-indacene-1-yl][2-methyl-4-(3',5'-5 ditert-butyl-phenyl)-5-methoxy-6-tert-benzylidene-1-yl] zirconium dichloride.
[0174] Particularly desirable is rac-anti-dimethylsilanediyl[2-methyl-4,8-bis-(3',5'-dimethylphenyl)-1,5,6,7-tetrahydro-s indacen-1-yl] [2-methyl-4-(3',5'-dimethylphenyl)-5-methoxy-6-tert-benzylidene-1-yl] zirconium dichloride.
[0175] The ligands required to form the complex compounds and catalyst systems of the present invention can be synthesized by any process, and a skilled organic chemist may devise various synthesis protocols for the preparation of the necessary ligand materials. For example, WO2007 / 116034 discloses the necessary chemistry. Synthetic protocols can also generally be found in WO 2002 / 02576, WO 2011 / 135004, WO 2012 / 084961, WO 2012 / 001052, WO 2011 / 076780, WO 2015 / 158790, and WO 2018 / 122134. In particular, refer to WO 2019 / 179959, which describes the most preferred catalyst of the present invention.
[0176] Co-catalyst
[0177] In order to form active catalytic chemical species, it is generally necessary to use a co-catalyst, as is well known in the art.
[0178] According to the present invention, a co-catalyst system comprising a boron-containing co-catalyst and / or an aluminoxan co-catalyst is used together with the metallocene catalyst complex defined above.
[0179] The aluminoxane co-catalyst can be one of the chemical formulas (II):
[0180]
[0181] In chemical formula (II), n is typically 6 to 20, and R has the following meaning.
[0182] Aluminoxan is formed upon the partial hydrolysis of organoaluminum compounds, e.g., those with the chemical formulas AlR3, AlR2Y, and Al2R3Y3, where R is, e.g., C1-C 10 Alkyl, preferably C1-C5 alkyl, or C3-C 10 Cycloalkyl, C7-C 12 It may be arylalkyl or alkylaryl and / or phenyl or naphthyl, and Y is hydrogen, halogen, preferably chlorine or bromine, or C1-C 10 It may be an alkoxy, preferably a methoxy or ethoxy. The resulting oxygen-containing aluminoxane is generally not a pure compound, but a mixture of oligomers of formula (II).
[0183] A preferred aluminoxan is methylaluminoxan (MAO). Since the aluminoxan used as a co-catalyst according to the present invention is not a pure compound due to the manufacturing method, the molar concentration of the aluminoxan solution below is based on the aluminum content.
[0184] According to the present invention, a boron-containing co-catalyst may be used instead of an aluminoxan co-catalyst, or an aluminoxan co-catalyst may be used together with a boron-containing co-catalyst.
[0185] Those skilled in the art will know that when using a boron-based co-catalyst, it is common practice to pre-alkylate the complex by reacting it with an aluminum alkyl compound such as TIBA. This procedure is well known, and suitable aluminum alkyls such as Al(C1-C6alkyl)3, for example, can be used. Preferred aluminum alkyl compounds are triethylaluminum, tri-isobutylaluminum, tri-isohexylaluminum, tri-n-octylaluminum, and tri-isooctylaluminum.
[0186] Alternatively, when a borate co-catalyst is used, the metallocene catalyst complex is an alkylated version, and for example, a dimethyl or dibenzyl metallocene catalyst complex may be used.
[0187] The boron-based co-catalysts of interest include those of formula (III):
[0188]
[0189] In formula (III), Y is the same or different hydrogen atom, an alkyl group having 1 to about 20 carbon atoms, an aryl group having 6 to about 15 carbon atoms, an alkylaryl, arylalkyl, haloalkyl or haloaryl having 1 to 10 carbon atoms in the alkyl radical and 6 to 20 carbon atoms in the aryl radical, or fluorine, chlorine, bromine or iodine. The preferred options are trifluoroborane, triphenylborane, tris(4-fluorophenyl)borane, tris(3,5-difluorophenyl)borane, tris(4-fluoromethylphenyl)borane, tris(2,4,6-trifluorophenyl)borane, tris(pentafluorophenyl)borane, tris(tolyl)borane, tris(3,5-dimethylphenyl)borane, tris(3,5-difluorophenyl)borane, and / or tris(3,4,5-trifluorophenyl)borane.
[0190] Tris(pentafluorophenyl)borane is particularly preferred.
[0191] However, it is preferable to use a compound containing a borate, that is, a borate 3+ ion. Such ionic co-catalysts preferably include non-coordinating anions such as tetrakis(pentafluorophenyl)borate and tetraphenylborate. Suitable counterions are protonated amine or aniline derivatives such as methylammonium, anilinium, dimethylammonium, diethylammonium, N-methylanilinium, diphenylammonium, N,N-dimethylanilinium, trimethylammonium, triethylammonium, tri-n-butylammonium, methyldiphenylammonium, pyridinium, p-bromo-N,N-dimethylanilinium, or p-nitro-N,N-dimethylanilinium.
[0192] Surprisingly, it was found that certain boron co-catalysts are particularly preferred. Therefore, the preferred borate used in the present invention contains trityl ions. Thus, the use of N,N-dimethylammonium-tetrakispentafluorophenylborate and Ph3CB(PhF5)4 and analogs is particularly preferred.
[0193] A preferred co-catalyst is aluminoxan, more preferably methylaluminoxan, a combination of aluminoxan and Al-alkyl, a boron or borate co-catalyst, or a combination of aluminoxan and a boron-based co-catalyst.
[0194] The catalyst system of the present invention is used in a supported form. The particle support material used is a mixed oxide, such as silica or silica-alumina, in particular silica. The use of a silica support is preferred. A skilled practitioner knows the procedures required to support a metallocene catalyst.
[0195] In a preferred embodiment, the catalyst system corresponds to ICS3 of WO 2020 / 239598 A1.
[0196] The method preferably further comprises the step of separating the polymer fraction from the polymerization mixture obtained in the final polymerization step in the presence of other components, such as additional polymeric components and / or additives as described herein, to obtain a polypropylene composition. Post-reactor treatment steps are well established in the art.
[0197] In one embodiment, the present invention relates to a polypropylene composition obtainable, more preferably obtained, through a method as described herein, as described above. All preferred embodiments and alternative positions given for the polypropylene compositions above and below are applicable to the processes of the present invention.
[0198] Items and Uses
[0199] In a third aspect, the present invention relates to an article comprising a polypropylene composition as described above or below, and to the use of a polypropylene composition as described above or below for the production of the article.
[0200] The article is preferably an injection-molded article or a molded article such as a fiber-reinforced composite.
[0201] The article may be an automobile article comprising a polypropylene composition as described above or below.
[0202] The article may also be a packaging article, preferably a thin-walled packaging article, a small container including, for example, a plastic cup, a bucket and a lid, and may be for food packaging including, for example, a polypropylene composition as described above or below.
[0203] In one embodiment, the composition of the article may include fibers such as glass fibers or carbon fibers. If fibers are present in the composition of the article, the amount of fibers is in the range of 5 to 40 weight percent based on the composition of the article.
[0204] In another embodiment, the composition of the article may include a mineral filler such as talc or mica. If a mineral filler is present in the composition of the article, the amount of the filler is in the range of 5 to 40 weight percent based on the composition of the article.
[0205] Experimental section
[0206] The following embodiments are included to demonstrate specific aspects and embodiments of the invention as described in the claims. However, those skilled in the art should understand that the following description is merely illustrative and should not be construed as limiting the invention in any way.
[0207] 1. Decision method
[0208] MFR 2(230℃) It was measured according to ISO 1133 at 230℃ and a 2.16 kg load.
[0209] CRYSTEX
[0210] Determination of crystalline and soluble fractions and their respective characteristics (IV and ethylene content)
[0211] The crystalline fraction (CF) and soluble fraction (SF) of the polypropylene (PP) composition, as well as the comonomer content and intrinsic viscosity of each fraction, were analyzed using the CRYSTEX instrument Polymer Char (Valencia, Spain). Detailed information on the techniques and methods can be found in the literature (Ljiljana Jeremic, Andreas Albrecht, Martina Sandholzer & Markus Gahleitner (2020) Rapid characterization of high-impact ethylene-propylene copolymer composition by crystallization extraction separation: comparability to standard separation methods, International Journal of Polymer Analysis and Characterization, 25:8, 581-596).
[0212] The crystalline and amorphous fractions were separated through a temperature cycle of dissolution at 160°C, crystallization at 40°C, and redissolution in 1,2,4-trichlorobenzene at 160°C. Quantification of SF and CF and determination of ethylene content (C2) were performed using an integrated infrared detector (IR4), and an online 2-capillary viscometer was used to determine intrinsic viscosity (iV).
[0213] The IR4 detector has two different bands (CH3 stretching vibrations (approx. 2960 cm⁻¹) that play a role in determining the concentration and ethylene content of ethylene-propylene copolymer. -1 (center) and CH stretching vibration (2700 to 3000 cm-1 It is a multi-wavelength detector that measures IR absorbance at ). The IR4 detector is for known ethylene content of 2 wt% to 69 wt% ( 13 A series of eight EP copolymers were calibrated within the range (measured by C-NMR) and varied in concentration from 2 to 13 mg / ml, respectively. To simultaneously verify both concentration and ethylene content—two characteristics—for the various polymer concentrations expected during Crystex analysis, the following calibration equation was applied:
[0214]
[0215]
[0216] The constants a to e in Equation 1 and the constants a to f in Equation 2 were determined using least squares regression analysis.
[0217] CH3 / 1000C was converted to ethylene content, weight%, using the following formula:
[0218]
[0219] The amounts of the soluble fraction (SF) and the crystalline fraction (CF) correlated with the amount of "xylene cold solubles (XCS)" and, respectively, the xylene cold insolubles (XCI) fraction when determined according to the standard gravimetric analysis method in accordance with ISO 16152 via XS correction. XS correction was achieved by testing various EP copolymers with XS content ranging from 2 to 31 wt%. The determined XS correction was linear:
[0220]
[0221] The intrinsic viscosity (IV) of the parent EP copolymer and its soluble and crystalline fractions was determined using an online 2-capillary viscometer and correlated with the corresponding iV determined by the standard method of decalin according to ISO 1628-3. Calibrations were performed using various EP-PP copolymers with iV = 2 to 4 dl / g. The determined calibration curves were linear:
[0222]
[0223] The weight of the samples to be analyzed was measured at concentrations ranging from 10 mg / ml to 20 mg / ml. To avoid the injection of gels and / or polymers that are insoluble in TCB at 160°C, such as PET and PA, the weighed samples were packed in stainless steel mesh MW 0.077 / D 0.05 mmm.
[0224] 1,2,4-TCB containing 250 mg / l of 2,6-tert-butyl-4-methylphenol (BHT) as an antioxidant was automatically filled into a vial, and the sample was dissolved at 160°C for typically 60 minutes while continuously stirring at 400 rpm until completely dissolved. To prevent sample degradation, the polymer solution was covered with an N2 atmosphere during dissolution.
[0225] A defined volume of sample solution was injected into a column filled with an inert support, where crystallization of the sample and separation of the soluble fraction from the crystalline portion occurred. This process was repeated twice. During the first injection, the entire sample was measured at high temperature to determine the iV [dl / g] and C2 [wt%] of the PP composition. During the second injection, the soluble fraction (low temperature) and crystalline fraction (high temperature) were measured according to the crystallization cycle (wt% SF, wt% C2, iV).
[0226] Xylene cold soluble (XCS, wt%) It was determined at 25℃ according to ISO 16152; 1st edition; 2005-07-01.
[0227] intrinsic viscosityIt was measured according to DIN ISO 1628 / 1, October 1999 (in decalin at 135℃).
[0228] Quantification of Microstructure by NMR Spectroscopy - Ethylene Content in HECO
[0229] The comonomer content of the polymer was quantified using quantitative nuclear magnetic resonance (NMR) spectroscopy. 13 C{ 1 H} NMR spectrum, 1 H and 13 For each of C, recordings were made in the solution state using a Bruker Advance III 400 NMR spectrophotometer operating at 400.15 and 100.62 MHz. For all pneumatics, nitrogen gas was used at 125°C. 13 All spectra were recorded using an optimized 10 mm extended temperature probe head. Approximately 200 mg of the substance was mixed with 3 ml of 1,2-tetrachloroethane- chromium-(III)-acetylacetonate (Cr(acac)3). d 2 (TCE- d 2It was dissolved in ) to yield a 65 mM relaxant solution in the solvent (Singh, G., Kothari, A., Gupta, V., Polymer Testing 28 5 (2009), 475). To ensure a homogeneous solution, after the initial sample preparation in the heat block, the NMR tube was further heated in a rotary oven for at least 1 hour. Upon insertion into the magnet, the tube was rotated at 10 Hz. This setup was selected primarily for high resolution and was quantitatively required for accurate quantification of ethylene content. Standard single-pulse excitation without NOE was used with an optimized tip angle, a 1 second recycle delay, and a bi-level WALTZ16 decoupling scheme (Zhou, Z., Kuemmerle, R., Qiu, X., Redwine, D., Cong, R., Taha, A., Baugh, D. Winniford, B., J. Mag. Reson. 187 (2007) 225; Busico, V., Carbonniere, P., Cipullo, R., Pellecchia, R., Severn, J., Talarico, G., Macromol. Rapid Commun. 2007, 28, 1128). A total of 6,144 (6 k) transients were acquired per spectrum.
[0230] Quantitative 13 C{ 1The H} NMR spectra were processed and integrated using a proprietary computer program, and relevant quantitative characteristics were determined from the integral. All chemical shifts were indirectly referenced to the central methylene group of the ethylene block (EEE) at 30.00 ppm using the chemical shift of the solvent. This approach allowed for similar references even when this structural unit was absent. Quantitative signals corresponding to ethylene incorporation were observed (Cheng, HN, Macromolecules 17 (1984), 1950).
[0231] Using the characteristic signal corresponding to the observed 2,1 erythroreggio defect (as described in L. Resconi, L. Cavallo, A. Fait, F. Piemontesi, Chem. Rev. 2000, 100 (4), 1253, in Cheng, HN, Macromolecules 1984, 17, 1950, and WJ. Wang and S. Zhu, Macromolecules 2000, 33 1157), it was necessary to correct for the influence of the regio defect on the determined properties. No characteristic signal corresponding to other types of regio defects was observed.
[0232] The comonomer fraction was prepared using the method of Wang et al. (Wang, WJ., Zhu, S., Macromolecules 33 (2000), 1157) 13 C{ 1 Quantification was performed through the integration of multiple signals across the entire spectral region of the H} spectrum. This method was selected due to its strong properties and ability to explain the presence of regiodefects if necessary. By slightly adjusting the integral region, applicability was increased across the entire range of encountered comonomer content.
[0233] For systems in which only ethylene isolated from the PPEPP sequence is observed, the method of Wang et al. was modified to reduce the influence of non-zero integrals in sites known to be non-existent. This approach reduced the overestimation of ethylene content for these systems, which was achieved by reducing the number of sites used to determine the absolute ethylene content:
[0234]
[0235] By using parts of this set, the corresponding integral equation is derived using the same notation as that used in Wang et al.'s paper:
[0236]
[0237] (Wang, WJ., Zhu, S., Macromolecules 33 (2000), 1157). The equation used for absolute propylene content was not modified.
[0238] The mole percentage of comonomer incorporation was calculated from the mole fraction:
[0239]
[0240] The mole percentage of comonomer incorporation was calculated from the mole fraction:
[0241]
[0242] The distribution of comonomer sequences at the triad level was determined according to the analysis method of Kakugo et al. (Kakugo, M., Naito, Y., Mizunuma, K., Miyatake, T. Macromolecules 15 (1982) 1150). This method was selected for its potent properties and integration region, which were slightly adjusted to increase applicability to a wider range of comonomer content.
[0243] Inflection coefficient80 x 10 x 4 mm injection molded according to EN ISO 1873-2 3 It was determined at 3-point bending according to ISO 178 on an injection molded test specimen.
[0244] Sharpy Notch Impact strength 80 x 10 x 4 mm injection molded according to EN ISO 1873-2 3 It was determined according to ISO 179-1 eA at 23°C on an injection molded test specimen.
[0245] DSC Analysis, Melting Temperature (Tm) and Crystallization Temperature (Tc):
[0246] The values were determined on 5 to 7 mg samples using a TA Instrument Q2000 differential scanning calorimeter (DSC). The DSC was performed according to ISO 11357 / Part 3 / Method C2 in a heating / cooling / heating cycle at a scan rate of 10°C / min in a temperature range of -30°C to +225°C. The crystallization temperature (Tc) and crystallization enthalpy (Hc) were determined from the cooling step, while the melting temperature (Tm) and melting enthalpy (Hm) were determined from the second heating step.
[0247] VOC value and FOG value Samples of injection molded plaques were prepared in accordance with EN ISO 19069-2:2016 and measured according to VDA 278 (October 2011; thermal desorption analysis of organic emissions for the characteristics of non-metallic materials for automobiles, VDA Verband der Automobilindustrie). The plaques were packaged in aluminum composite foil immediately after production and the foil was sealed.
[0248] According to VDA 278 October 2011, the VOC value is defined as the "sum of immediately volatile to intermediate volatile substances." This is calculated in toluene equivalents. Using the method described in this recommendation, the maximum n-pentacosan(C 25 It enables the determination and analysis of the components within the boiling / eluting range of ).
[0249] The FOG value is defined as the "total sum of low-volatility components eluted from the residence time of n-tetradecane (including)." This is calculated in hexadecane equivalents. n-alkanes "C 14 "from "C 32 The components within the boiling range were determined and analyzed.
[0250] 2. Examples
[0251] The catalyst used in the polymerization process of all examples was Anti-dimethylsilanediyl[2-methyl-4,8-di(3,5-dimethylphenyl)-1,5,6,7-tetrahydro-s-indacene-1-yl][2-methyl-4-(3,5-dimethylphenyl)-5-methoxy-6-tert-benzylidene-1-yl] zirconium dichloride disclosed as MC-2 in WO 2019 / 179959 A1. The supported metallocene catalyst was produced similarly to IE2 in WO 2019 / 179959 A1.
[0252] The heterophase propylene copolymers of Examples IE1, IE2, and IE3 of the present invention and Comparative Example CE1 were prepared in a Borstar PP pilot apparatus equipped with a sequential process comprising a prepolymerization reactor, a loop reactor, and two gas phase reactors. The reaction conditions are summarized in Table 1.
[0253]
[0254]
[0255] For the production of polypropylene compositions of Examples IE1, IE2, and IE3 of the present invention and Comparative Example CE1, the heterophase propylene copolymers listed in Table 1 above were each combined with 1500 ppm of Irganox B215 (antioxidant 2:1 blend of Irgafos 168 (tris(2,4-ditert-butylphenyl)phosphite, CAS No.: 31570-04-4) and Irganox 1010 (pentaerythritol tetrakis[3-[3,5-di-tert-butyl-4-hydroxyphenyl]propionate], CAS No.: 6683-19-8, commercially available from BASF SE) and 500 ppm of calcium stearate (CAS No.: 1592-23-0, commercially available from B.R.L.C. GmbH under the trade name CEASIT-1).
[0256] Comparative Example CE2 is a heterogeneous polypropylene composition BJ400HP (commercially available from Borealis AG).
[0257] The characteristics of the polypropylene compositions of Examples IE1 and IE2 and Comparative Examples CE1 and CE2 of the present invention are listed in Table 2 below.
[0258]
[0259] nm.m. = Not measured (CE1's VOG + FOG is estimated to be in the IE1 / IE2 range)
[0260] The polypropylene compositions of Examples IE1, IE2, and IE3 of the present invention exhibit a balance of higher MFR2 and better flexural modulus and Charpy NIS than Comparative Example CE1, as shown in the equations of the last two lines of Table 2.
[0261] The polypropylene composition of Comparative Example CE2 exemplifies the problems of Ziegler-Natta catalyzed high melt flow heterophase propylene copolymers. The high MFR2 of CE2 is accompanied by high VOC and FOG values. Although CE2 exhibits a high flexural modulus as indicated in the equations of the last two lines of Table 2, the balance of Charpy NIS and melt flow rate MFR2 is inferior compared to IE1 and IE2.
Claims
Claim 1 A polypropylene composition comprising both a crystalline fraction (CF) and a soluble fraction (SF) as determined by CRYSTEX QC analysis, wherein the soluble fraction (SF) is present in the polypropylene composition in an amount ranging from 10.0 to 35.0 wt%, or from 11.0 to 32.5 wt%, or from 12.0 to 30.0 wt% based on the total weight of the polypropylene composition, and has an intrinsic viscosity (iV(SF)) of at least 2.0 dl / g, or from 2.3 to 4.5 dl / g, or from 2.5 to 4.3 dl / g, and quantitative 13 A polypropylene composition having an ethylene content (C2(SF)) in the range of 14.0 to 29.0 wt%, or 17.0 to 26.0 wt%, or 19.0 to 24.0 wt% based on the total weight of the soluble fraction (SF) as determined by FT-IR spectroscopy corrected by C-NMR spectroscopy; the ratio of the intrinsic viscosity of the soluble fraction to the intrinsic viscosity of the crystalline fraction (iV(SF) / (iV(CF))) is in the range of 2.5 to 5.0, or 2.6 to 4.8; and the polypropylene composition having a melt flow rate MFR2 (230°C, 2.16 kg, ISO 1133) in the range of 105 to 320 g / 10 min, or 107 to 300 g / 10 min, or 110 to 280 g / 10 min. Claim 2 In claim 1, the crystalline fraction (CF) is present in the polypropylene composition in an amount ranging from 65.0 to 90.0 weight%, or from 67.5 to 89.0 weight%, or from 70.0 to 88.0 weight% based on the total weight of the polypropylene composition, has an intrinsic viscosity (iV(CF)) of 1.2 dl / g or less, or in the range of 0.4 to 1.1 dl / g, and is quantitative 13 A polypropylene composition having an ethylene content (C2(CF)) of 1.0 wt% or less, or in the range of 0 to 0.9 wt%, based on the total weight of the crystalline fraction (CF) as determined by FT-IR spectroscopy corrected by C-NMR spectroscopy. Claim 3 A polypropylene composition according to claim 1, comprising a heterophasic propylene copolymer comprising a semicrystalline matrix phase and an elastomeric phase dispersed on the matrix, wherein the polypropylene composition comprises an amount of the heterophasic propylene copolymer in the range of 93.0 wt% to 100 wt%, or 95.0 wt% to 99.9 wt%, or 96.5 wt% to 99.8 wt%. Claim 4 In claim 1, the composition comprises a fraction (XCS) soluble in cold xylene in an amount ranging from 8.0 to 32.0 wt%, or from 9.0 to 30.0 wt%, or from 10.0 to 28.0 wt% based on the total weight of the polypropylene composition at 25°C, wherein the XCS fraction has the following characteristics: · an intrinsic viscosity (iV(XCS)) of at least 2.2 dl / g, or in the range of 2.3 to 4.6 dl / g, or in the range of 2.5 to 4.4 dl / g, and · quantitative 13 A polypropylene composition having an ethylene content (C2(XCS)) in the range of 15.0 to 30.0 wt%, or 18.0 to 27.0 wt%, or 20.0 to 25.0 wt% based on the total weight of the soluble fraction (SF) as determined by FT-IR spectroscopy corrected by C-NMR spectroscopy. Claim 5 In claim 1, an injection molded test specimen (80 x 10 x 4 mm) produced in accordance with EN ISO 1873-2 3 A polypropylene composition having a flexural modulus (FM) in the range of 800 MPa to 1500 MPa or 850 MPa to 1450 MPa when determined according to ISO 178. Claim 6 In claim 1, having a bending coefficient (FM) satisfying the following inequality with respect to the amount of soluble fraction (SF): or or or At this time, FM [MPa] is the flexural modulus of the polypropylene composition and is expressed as MPa, and the amount (SF) [weight%] is the amount of the soluble fraction (SF) in the polypropylene composition and is expressed as weight%, the polypropylene composition. Claim 7 In paragraph 1, the following characteristics: · Quantitative 13 Total ethylene (C2) content in the range of 2.0 to 5.5 wt% or 2.5 to 5.0 wt% based on the total weight of the polypropylene composition, as determined by FT-IR spectroscopy corrected by C-NMR spectroscopy; melting temperature (Tm) in the range of 150°C to 162°C or 152°C to 160°C, as determined by DSC according to ISO 3146 (Part 3, Method C2); crystallization temperature (Tc) in the range of 110°C to 130°C or 115°C to 125°C, as determined by DSC according to ISO 3146 (Part 3, Method C2); injection molded specimen (80 x 10 x 4 mm) produced according to EN ISO 1873-2 3 2.5 to 15.0 kJ / m² when determined according to ISO 179 / eA on ) 2 Range, or 3.0 to 12.0 kJ / m² 2 A polypropylene composition having one or more, or all, of: a Charpy notch impact strength at 23°C in the range; a volatile organic compound (VOC) content of 50 μg / g or less, or 40 μg / g or less, or 35 μg / g or less as determined according to VDA 278; and / or a FOG content of 300 μg / g or less, or 250 μg / g or less, or 225 μg / g or less as determined according to VDA 278. Claim 8 A method for producing a polypropylene composition according to any one of claims 1 to 7, comprising: a) polymerizing propylene in a first polymerization reactor in the presence of a single-site catalyst system to produce a first propylene polymer fraction; b) transferring a polymerization mixture comprising the single-site catalyst system and the first propylene polymer fraction from the first polymerization reactor to a second polymerization reactor; c) polymerizing propylene in a second polymerization reactor in the presence of a single-site catalyst system to produce a second propylene polymer fraction; d) transferring a polymerization mixture comprising the single-site catalyst system and the first and second propylene polymer fractions from the second polymerization reactor to a third polymerization reactor; e) polymerizing propylene and ethylene in a third polymerization reactor in the presence of a single-site catalyst system to produce a third propylene-ethylene copolymer fraction; and f) comprising the single-site catalyst system, the first and second propylene polymer fractions and the third propylene-ethylene copolymer fraction. A method comprising: a step of withdrawing the polymerization mixture from a third polymerization reactor; and g) a step of obtaining a polymer composition comprising first and second propylene polymer fractions and a third propylene-ethylene copolymer fraction. Claim 9 In claim 8, the single-site catalytic system (i) is a metallocene complex of formula (I): In chemical formula (I), each X is independently a sigma-donor ligand, L is a divalent bridge selected from -R'2C-, -R'2C-CR'2-, -R'2Si-, -R'2Si-SiR'2-, and -R'2Ge-, and each R' is independently a C1-C that optionally contains a hydrogen atom or one or more heteroatoms from groups 14 to 16 of the periodic table. 20 - It can be a hydrocarbyl group or a fluorine atom, or optionally two R' groups can be taken together to form a ring, and each R 1 may be independently the same or different, and may be hydrogen, linear or branched C1-C6-alkyl groups, C 7-20 -arylalkyl, C 7-20 -alkylaryl group or C 6-20 - It is an aryl or OY group, and Y is C 1-10 - It is a hydrocarbil group, and optionally 2 adjacent R 1 The group may be a part of a ring containing a phenyl carbon to which it is bonded, and each R 2 It may be independently the same or different, and CH2-R 8 It is, and at this time R 8 is H or linear or branched C 1-6 -alkyl group, C 3-8 -cycloalkyl group, C 6-10 -Arilgigo,R 3 is a linear or branched C1-C6-alkyl group, C 7-20 -arylalkyl, C 7-20 -alkylaryl group or C6-C 20 - It is Arilgi, and R 4 is C(R 9 It is stage 3, and at this time R 9 is a linear or branched C1-C6-alkyl group, and R 5 It is an aliphatic C1-C that selectively contains hydrogen or one or more heteroatoms from Groups 14 to 16 of the periodic table. 20 - It is a hydrocarbyl group; R 6 Aliphatic C1-C that optionally contains hydrogen or one or more heteroatoms from Groups 14 to 16 of the periodic table 20 - Hydrocarbyl group or; R 5 and R 6 They can be taken together to form a 5-membered saturated carbon ring, which consists of n groups R 10 Optionally substituted by, where n is 0 to 4; and each R 10 is identical or different, and C1-C 20 - A C1-C optionally containing a hydrocarbyl group, or one or more heteroatoms belonging to groups 14 to 16 of the periodic table 20 - May be a hydrocarbyl group; R 7 H or a linear or branched C1-C6-alkyl group or 1 to 3 R 11 It is an aryl or heteroaryl group having 6 to 20 carbon atoms that is selectively substituted by a group, and each R 11 may be independently the same or different, and may be hydrogen, linear or branched C1-C6-alkyl groups, C 7-20 -arylalkyl, C 7-20 -alkylaryl group or C 6-20 - It is an aryl or OY group, and Y is C 1-10 - A hydrocarbyl group, (ii) a co-catalyst system comprising a boron-containing co-catalyst and / or an aluminoxane co-catalyst, and (iii) a silica support, a method. Claim 10 In paragraph 8, the method wherein the first and / or second propylene polymer fraction(s) are propylene homopolymer fraction(s). Claim 11 In claim 8, the method having a melt flow rate MFR2 (230°C, 2.16 kg, ISO 1133) of the first propylene polymer fraction in the range of 1000 to 15000 g / 10 min, or 1100 to 13500 g / 10 min, or 1250 to 11500 g / 10 min. Claim 12 The method of claim 8, wherein the combined first propylene polymer fraction and the second propylene polymer fraction have a melt flow rate MFR2 (230°C, 2.16 kg, ISO 1133) in the range of at least 1000 g / 10 min, or 1200 to 9000 g / 10 min, or 1500 to 8000 g / 10 min. Claim 13 A method according to claim 8, wherein the combined first propylene polymer fraction and the second propylene polymer fraction comprise a fraction (XCS) soluble in cold xylene in an amount of 2.0 weight% or less, or in the range of 0.1 to 1.5 weight%, based on the total weight of the combined first propylene polymer fraction and the second propylene polymer fraction at 25°C. Claim 14 An article comprising a polypropylene composition according to any one of claims 1 to 7. Claim 15 A method for increasing the melt flow rate of a polymer composition, comprising the step of providing a polypropylene composition according to any one of claims 1 to 7 as a compound base for the polymer composition.
Citation Information
Patent Citations
Heterophasic polypropylene with high flowability and excellent low temperature impact properties
EP2075284A1
Heterophasic polypropylene with improved puncture respectively impact strength / stiffness balance
KR1020170062540A
polypropylene composition
KR1020200083628A
Heterophasic polypropylene compositions comprising a recycled material as modifier with an improved balance of mechanical properties
WO2021144404A1
